Violins & Shovels: The WPA Arts Projects - Meltzer, Milton 1915-2009 (New York Delacorte, 1976)
Examines art projects run during the 1930's which were funded by the Work Projects Administration.
Bibliography: p. [150]-153.
Keywords: 20th Century (1901-2000); Fine art; USA